Modulatory Effects of Clopidogrel on Vascular Response in the Human Internal Mammary Artery: An In Vitro Study - Öz, Zeynep Dila; Kaçar, Emine; Özgüler, İbrahim Murat; Üstünel, Latif (Kare Publ, 2026)
Background: Coronary artery disease (CAD) is one of the leading causes of mortality worldwide, and coronary artery bypass grafting (CABG) is frequently preferred as a surgical approach in advanced cases. The most commonly used graft material in CABG, the left internal mammary artery (LIMA), is considered the gold standard due to its high longterm patency rates. Clopidogrel, an antithrombotic agent widely used in CABG patients that targets P2Y12 receptors on platelets, has also been suggested to influence vascular responses due to the presence of these receptors in vascular smooth muscle cells. However, the direct vascular effects of clopidogrel on LIMA remain unknown. Methods: In this study, isolated LIMA segments obtained from 20 patients undergoing CABG were evaluated to compare the contractile responses induced by phenylephrine (PE; 10-9-10-4 M) and the endothelium-independent relaxation responses induced by sodium nitroprusside (SNP; 10-9-10-4 M), before and after pretreatment with 0.1 mu M clopidogrel. Result: In clopidogrel-treated LIMA segments, all PE-induced contractile responses were significantly attenuated, whereas SNP-induced relaxation was enhanced at low and moderate concentrations; however, this relaxant effect was diminished at the highest dose. Conclusion: This biphasic effect observed in LIMA segments suggests that clopidogrel may act not only as an antithrombotic agent, but also as a direct modulator of vascular tone. These findings indicate that the local vascular effects of clopidogrel should be considered in developing therapeutic strategies aimed at maintaining graft patency following CABG.
Keywords: Antiplatelet agents; bypass; coronary heart disease; internal mammary artery; organ bath